Complete poems and selected letters of Michelangelo - Michelangelo Buonarroti, 1475-1564 (Princeton paperbacks., 1980)
Considers how the surviving letters of Michelangelo have a distinctly public character and show us the external man. Many of them are business letters and are thus in reference to his art and sculpture, creating a timeline for his work. In contrast, much of Michelangelo's poetry is more personal, showing his emotional attachment to his family.